2013
DOI: 10.5851/kosfa.2013.33.4.508
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Taste-active Compounds between Hanwoo Longissimus and Semitendinosus Muscles and Its Comparision with Angus Longissimus Beef Muscle

Abstract: Taste-active compounds (e.g., amino acids and nucleotides) play an important role in contribution to the gustatoty sensation of food. The current study aimed to examine the differences in taste-active compounds between different beef muscles, breeds and aging periods. We have chosen the longissimus dorsi and semitendinosus muscles of Hanwoo breed and longissimus dorsi muscle of Angus breed for the investigation of the aforementioned compounds. Hanwoo muscles were aged for 7 or 28 d, and Angus samples were aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The increase in inosine content can be explained by the conversation of IMP during aging. Dashmaa et al (2013) reported a negative relationship between IMP and inosine and hypoxanthine in Hanwoo muscle, both of which are produced by endogenous enzymes or microorganisms from IMP during aging.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in inosine content can be explained by the conversation of IMP during aging. Dashmaa et al (2013) reported a negative relationship between IMP and inosine and hypoxanthine in Hanwoo muscle, both of which are produced by endogenous enzymes or microorganisms from IMP during aging.…”
Section: Resultsmentioning
confidence: 99%
“…FAA are known as the important compounds responsible for the sensory quality of cooked meat, especially umami ( Dashmaa et al, 2013 ; Jayasena et al, 2013 ). The outcome of our analysis depicts that nine-teen FAAs were detected in the samples ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The FFA content in the samples was analyzed following the procedure as described by Dashmaa et al (2013) with suitable modifications. Briefly, 2.5 g of each sample was homogenized with 5 mL DDW at 5,300×g for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More to the point, the postmortem aging causes an increased muscle protein breakdown by endogenous proteases, resulting in formations of small peptides and free amino acids which are the important flavor precursors (Dashdorj et al, 2013; Koutsidis et al, 2008; Reina et al, 2014). During cooking, these precursors (e.g., amino acids) react with other components (e.g., reducing sugars) to produce a variety of volatile aroma compounds which subsequently contribute to the typical flavor characteristics of cooked beef (Calkins and Hodgen, 2007; Elmore et al, 2002; Mottram 1994; Van Ba et al, 2013).…”
Section: Introductionmentioning
confidence: 99%